I am not a Sportsman: the characteristics of identity construction in Traditional Chinese Martial Arts groups - Long Xi (Cogent Social Sciences, 2024)
Against the backdrop of sports globalization, Chinese martial arts are influenced by the integration of diverse cultures, making the identity of martial arts communities a topic worthy of attention. Although Chinese scholars have conducted extensive discussions on the issues of Chinese martial arts communities, most of these discussions have been based on reviews and quantitative methods. There is a lack of exploration into the construction of identity among traditional Chinese martial arts communities and the factors affecting identity recognition, as well as a lack of focus on internal group conflicts. The purpose of this paper is to survey how Chinese martial artists define their own identity and how factors inside and outside the group influence their perception of identity. The study adopts grounded theory based on constructivist methodology, interviewing 28 participants (15 traditional martial artists, 6 competitive martial athletes, 5 decision-makers and managers, and 2 university researchers). The research results have established a theoretical model of identity construction based on traditional martial arts communities, describing the subjective interpretation of the complex process by which traditional Chinese martial arts communities form their identity definition. The model demonstrates the impact of individual, intra-group, and extra-group dimensions on identity recognition. The foundation of identity construction for traditional Chinese martial arts communities is the individual’s perception of martial arts, while factors inside and outside the group have a shaping effect on the identity recognition of group members. The study reveals that the process of identity construction is complex and highly related to cultural influences, rather than being singular. This research helps stakeholders better understand the characteristics of the identity of traditional Chinese martial arts communities and provides a foundation for future research on Chinese martial arts communities and cultural integration.